Halogenated organic pollutants in aquatic, amphibious, and terrestrial organisms from an e-waste site: Habitat-dependent accumulation and maternal transfer in watersnake. (October 2018) - Liu, Yu; Luo, Xiao-Jun; Huang, Li-Qian; Tao, Lin; Zeng, Yan-Hong; Mai, Bi-Xian
Abstract: Dichlorodiphenyltrichloroethanes (DDTs), Polychlorinated biphenyls (PCBs), and halogenated flame retardants (HFRs) were measured in aquatic, amphibious, and terrestrial wildlife collected from an e-waste contaminated pond and its surrounding region. The species-specific bioaccumulation and maternal transfer of chemicals in the watersnake were investigated. Total concentrations of target chemicals ranged from 1.3 × 10 3 to 4.8 × 10 5  ng g −1 lipid weight. PCBs were the predominant (72–95%) contaminants, followed by polybrominated biphenyl ethers (PBDEs, 4–27%). The concentrations of PCBs and HFRs except decabromodiphenyl ethane (DBDPE) were higher in aquatic organisms and terrestrial birds than in amphibians and lizards. Relatively high DDT levels were observed in the terrestrial birds and toads, but high DBDPE was found in the aquatic species except for waterbird eggs. Species-specific congeners profiles for PCB and PBDE and isomeric composition for dechlorane plus were observed. These results indicated a habitat-dependent accumulation among different species. Maternal transfer examined by the ratio of egg to carcass for watersnakes indicated multi-linear correlations between maternal transfer potential and octanol-water partition coefficient (log K OW ) of chemicals. The same maternal transfer efficiencies were found for chemicals with log K OW between 6 and 8, then the maternal transfer potential rapidly decreased with increasing of log K OW. Graphical abstract: Highlights: PCB was the predominant contaminant, followed by PBDE in wildlife from an e-waste site. Different contaminant patterns were observed among aquatic, amphibious, and terrestrial wildlife. The maternal transfer of HOPs in watersnake was firstly reported. Abstract : Different contaminant patterns of HOPs were observed among aquatic, amphibious, and terrestrial wildlife, and maternal transfer in watersnake was firstly reported.